Hearing Loss and Irritability Reporting Without Vestibular Differences in Explosive Breaching Professionals - Modica, Claire M.; Johnson, Brian R.; Zalewski, Christopher; King, Kelly; Brewer, Carmen; King, John E.; Yarnell, Angela M.; LoPresti, Matthew L.; Walker, Peter B.; Dell, Kristine C.; Polejaeva, Elena; Quick, Alycia; et al. (Frontiers in Neurology, 2020)
Background: Blast exposure is a potential hazard in modern military operations and training, especially for some military occupations. Helmets, peripheral armor, hearing protection, and eye protection worn by military personnel provide some acute protection from blast effects but may not fully protect personnel against cumulative effects of repeated blast overpressure waves experienced over a career. The current study aimed to characterize the long-term outcomes of repeated exposure to primary blast overpressure in experienced career operators with an emphasis on the assessment of hearing and vestibular outcomes. Methods: Participants included experienced “breachers” (military and law enforcement explosives professionals who gain entry into structures through controlled detonation of charges) and similarly aged and experienced “non-breachers” (non-breaching military and law enforcement personnel). Responses to a clinical interview and performance on audiological and vestibular testing were compared. Results: Hearing loss, ringing in the ears, irritability, and sensitivity to light or noise were more common among breachers than non-breachers. Breachers reported more combat exposure than non-breachers, and subsequently, memory loss and difficulty concentrating were associated with both breaching and combat exposure. Vestibular and ocular motor outcomes were not different between breachers and non-breachers. Conclusion: Hearing-related, irritability, and sensitivity outcomes are associated with a career in breaching. Future studies examining long-term effects of blast exposure should take measures to control for combat exposure.